Investigation flipped classroom effectiveness in teaching anatomy: A systematic review - Kazeminia, Mohsen; Salehi, Leili; Khosravipour, Masoud; Rajati, Fatemeh (Journal of professional nursing, 2022)
In the Filliped Classroom (FC), the educational environment changes from a large place to an individual learning space and presents curriculum content outside the classroom, engaging learners. Several preliminary studies have been conducted to evaluate the effectiveness of the FC in anatomy curricular, there are discrepancies between their results. Therefore, the present study was conducted to determine the efficiency of FC in anatomy courses using systematic review. In the current systematic review, all documents related to the FC in the anatomy teaching were searched using validated MeSH terms and their synonyms including “Flipp*”, “Backwards Classroom”, “Reverse Instruction”, “Reverse Teaching”, “Anatomy” in the Embase, ProQuest, Scopus, PubMed, Web of science (WoS). Google Scholar search engine and two local resources of Scientific Information Database (SID), MagIran, were also searched. The records were considered without time limitation until April 2021. A total of 1169 articles were found and after removing duplicate articles in different databases or unrelated to the inclusion criteria, finally 26 articles with a total sample size articles of the FC group of 2401 people were included in the study. According to the included studies the FC increases the level of self-confidence, improves academic achievement and students' interest and satisfaction, engages students in the learning and interactive activities, longevity and increases overall performance in anatomy curricular. The results of this systematic review show that FC is generally perceived positively, and it has some advantages including increasing self-confidence, academic achievement, interest, learning activity, interaction, satisfaction, and overall performance in anatomy curricular. Therefore, it is suggested that this method be considered as one of the methods in teaching anatomy curricular. [Display omitted] •The databases were reviewed without time limit until April 2021.•The flipped classroom increases self-confidence, increases grades, increases interest, activity in the class, interaction, satisfaction, longevity and increases overall performance in anatomy.•Further studies are needed to reduce the pretest stress, increase-learning objectives, better comprehension, break class ice, increase attention, reduce frustration, and reduce fatigue.